Local Government Fiscal Regulation in the EU: The Impact of Balanced Budget Rules - Beate Jochimsen; Christian Raffer (ZBW - Leibniz Information Centre for Economics, 2020)
In the past decades many European countries implemented numerical fiscal rules in order to strengthen fiscal discipline on all levels of government. This development was intensified by the financial crisis in 2008. Although plenty of research points to the discipline-enhancing effect of these rules on the national level, comparably little is known about their impact on local governments. This is even truer when it comes to the effect of specific rules like the so-called Balanced Budget Rule (BBR). With this contribution, we shed some light on the question if BBRs are an effective instrument to put local government budget balances on a sound footing. We estimate a dynamic fiscal reaction function within a LSDVC framework using a panel of 19 European countries over a period of 19 years (1997-2015). Although a potential endogeneity bias cannot be fully ruled out, the results suggest a discipline enhancing effect of BBRs over a range of different specifications. Other fiscal rules seem to be less important. Disentangling the effect of the mere existence of a BBR from its institutional implementation reveals that there is no significant effect for simply making a BBR part of an intergovernmental fiscal framework; what counts is its proper implementation in terms of characteristics like regulatory embeddedness, monitoring, enforcement, and media visibility.
Keywords: H62; H72; H83; 330